Parallel equalization schemes for Turbo equalizer - CHENG Xiang1; YUAN Dong-feng1 (Tongxin xuebao)
In order to reduce the equalization delay induced by iteration, two parallel methods were proposed respectively based on maximum a-posteriori probability （MAP） and linear minimum mean-squared error （LMMSE） equalization algo-rithm in Turbo equalization. Through theoretical analysis, simulation and hardware complexity discussion, it is concluded that the proposed two parallel equalization schemes can fully reduced the equalization delay with small hardware com-plexity and excellent performance.